PENGARUH PENAMBAHAN PLASTIK POLIPROPILENA TERHADAP YIELD DAN KUALITAS MINYAK NABATI HASIL PIROLISIS BONGGOL JAGUNG YANG MENGGUNAKAN CO2 SEBAGAI GAS PEMBAWA - Edgar, Justin; Supramono, Dijan (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2019)
Indonesia has potential sources for development of renewable fuels from agricultural wastes, one of which is corn cobs. Many researches have tried to convert corn cobs into a liquid fuel by pyrolysis, but the resulting bio-oil has a high oxygenate content, resulting in a low heating value. On the other hand, plastic waste has become a major problem for Indonesia, amounting to 5,4 million tons of waste per year. Around 16% of the total plastic waste is polypropylene, in which its high hydrogen/carbon ratio is an attractive hydrogen source for co-feeding with corn cobs in co-pyrolysis. Synergetic effect has been formed between the two, which has been proven to increase the yield and quality of the resulting bio-oil. Most co-pyrolysis process has been conducted with nitrogen as carrier gas. Its high price creates an economic barrier for commercial production of bio-fuel using co-pyrolysis method. It is proposed to substitute nitrogen with carbon dioxide. Beside of its low cost, carbon dioxide is known to have a heat-trapping effect, thus increasing the heat flux to particle feed during co-pyrolysis process. Three feed compositions during the process has been investigated to observe the effect of feed composition to the yield and quality of the non-polar (non-oxygenated) fraction of resulting bio-oil, which will be compared to commercial gasoline. Co-pyrolysis process was conducted in a stirred tank reactor with low heating rate of 5oC/min, maximum temperature of 500oC. Non-polar fraction of the resulting bio-oil has been characterized using GC-MS (gas chromatography-mass spectroscopy) and H-NMR (hydrogen-nuclear magnetic resonance). Bio-oil yield is lower compared to its counterpart when nitrogen is used as carrier gas, but H-NMR results shows that the non-polar fraction have a high branching index, low alkene and aromatic contents, which is potential to be used as a bio-fuel.